PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL PEMODERASI (Studi Pada Perusahaan Food and Beverage Tahun 2013-2017) - Anggita Langgeng Wijaya; Erlita Listyana Pancawati (Universitas PGRI Madiun, 2019)
The implementation of Corporate Social Responsibility is now very necessary. The purpose of this study is to explain the effect of CSR Disclosure (XI) on Company Value (Y), Profitability (X2) on Company Value (Y), and the role of Capital Structure (Z) as a moderating variable of the influence of CSR (XI) and Profitability (X2 ) of Company Value (Y).The sample in this study is a food and beverage company listed on the Indonesia Stock Exchange (BEI), in 2013-2017 whose financial statements contain corporate social responsibility activities. Data is taken through financial statements that will be sampled according to the desired criteria. This analysis technique uses statistical analysis, and regression analysis. The results of this study indicate that the Corporate Social Responsibility (CSR) variable has a positive and significant effect on Company Value, the Profitability Variable has a positive and significant effect on Company Value, the Capital Structure Variable significantly strengthens the effect of Corporate Social Responsibility (CSR) on Company Value, the Capital Structure Variable significantly strengthens the effect of Profitability on Company Value.Keywords: Corporate Social Responsibility (CSR) Disclosure, Profitability, Capital Structure, Company Value.